Prevalence and Prognostic Significance of Liver Fibrosis in Patients With Aneurysmal Subarachnoid Hemorrhage - Li, Tiangui; Wang, Peng; Gong, Xiao; Chong, Weelic; Hai, Yang; You, Chao; Kang, Juan; Fang, Fang; Zhang, Yu (Frontiers in Neurology, 2022)
Objectives To report the prevalence, clinical associations, and prognostic consequences of liver fibrosis in patients with aneurysmal subarachnoid hemorrhage (aSAH). Methods In a retrospective study of patients with aSAH, we evaluated three validated liver fibrosis indices and modeled them as continuous-exposure variables, including the aspartate aminotransferase/platelet ratio index (APRI), the fibrosis-4 (FIB-4) index, and the Forns index. The primary outcome was mortality at 90 days. We compared the addition of fibrosis indices to the predictors of the full Subarachnoid Hemorrhage International Trialists model. Results A total of 3,722 patients with aSAH were included in the study. According to the APRI, FIB-4 index, and Forns index, 21.7, 17.7, and 11.4% of patients had liver fibrosis. After adjusting for potential confounding factors, liver fibrosis indices were associated with increased 90-day mortality, with odds ratios of 1.35 (95% CI 1.02–1.77) for the FIB-4 index, 1.39 (95% CI.08–1.78) for APRI, and 1.53 (95% CI 1.11–2.12) for the Forns index. Similarly, high liver fibrosis indices were associated with an increased risk of rebleeding. However, the Forns index was not significantly associated with mortality and rebleeding. The addition of FIB-4 indices and APRI into the standard model improved the mortality prediction. Conclusions Liver fibrosis is common in patients with aSAH, and high liver fibrosis indices are associated with mortality and rebleeding. The addition of liver fibrosis indices to a standard clinical model significantly improves risk stratification.